El impacto de los entornos mediados y no mediados en las interacciones entre estudiantes universitarios: una revisión sistemática - Fosco Schmoele, Anaclara (2026)
As technology-mediated environments become increasingly prevalent in educational settings, understanding their impact on student interactions during learning processes is vital. Despite the growing integration of technology in education, there remains a significant gap regarding systematic reviews comparing various educational environments. Our research focused on conducting a systematic review of the effects of different settings on university students’ interactions. A comprehensive analysis of quasi-experimental and experimental studies was carried out to understand how mediated and non-mediated environments influence student learning interactions, with particular emphasis on academic and non-academic tasks. Following a meticulous selection process, we identified 16 pertinent articles. The findings revealed significant differences in interaction dynamics based on the type of environment utilized and demonstrated that, while the nature of the tasks did not significantly modify interaction patterns, the choice of environment played a crucial role in shaping these dynamics. In conclusion, this study underscores the necessity of carefully considering the unique advantages and challenges presented by both mediated and non-mediated environments in educational curriculum design. Integrating these insights into curriculum development may enable educators to more effectively tailor educational experiences that enhance student interaction and foster deeper learning. This approach is critical for maximizing the potential benefits of educational technologies and creating more engaging and effective learning environments.